Characterization of Aspergillus tamarii Strains From Human Keratomycoses: Molecular Identification, Antifungal Susceptibility Patterns and Cyclopiazonic Acid Producing Abilities - Homa, Mónika; Manikandan, Palanisamy; Szekeres, András; Kiss, Noémi; Kocsubé, Sándor; Kredics, László; Alshehri, Bader; Dukhyil, Abdul Aziz Bin; Revathi, Rajaraman; Narendran, Venkatapathy; Vágvölgyi, Csaba; Shobana, Coimbatore Subramanian; et al. (Frontiers in Microbiology, 2019)
Aspergillus tamarii appears to be an emerging aetiological agent of human keratomycoses in South India. The investigated strains were isolated from six suspected fungal keratitis patients attending a tertiary care eye hospital in Coimbatore (Tamil Nadu, India), and were initially identified by the microscopic examinations of the scrapings and the cultures. Our data suggest that A. tamarii could be easily overlooked when identification is carried out based on morphological characteristics alone, while the sequence analysis of the calmodulin gene can be used successfully to recognize this species accurately. According to the collected clinical data, ocular trauma is a common risk factor for the infection that gradually developed from mild to severe ulcers and could be healed with an appropriate combined antifungal therapy. Antifungal susceptibility testing revealed that A. tamarii strains are susceptible to the most commonly used topical or systemic antifungal agents (i.e., econazole, itraconazole and ketoconazole) except for natamycin. Moreover, natamycin proved to be similarly less effective than the azoles against A. tamarii in our drug interaction tests, as the predominance of indifferent interactions was revealed between natamycin and econazole and between natamycin and itraconazole as well. Four and five isolates of A. tamarii were confirmed to produce cyclopiazonic acid in RPMI-1640 – which is designed to mimic the composition of human extracellular fluids – and in yeast extract sucrose (YES) medium, respectively, which is a widely used culture medium for testing mycotoxin production. Although a ten times lower mycelial biomass was recorded in RPMI-1640 than in YES medium, the toxin contents of the samples were of the same order of magnitude in both types of media. There might be a relationship between the outcome of infections and the toxigenic properties of the infecting fungal strains. However, this remains to be investigated in the future.